LANDSCAPE OF THE RETAIL BUSINESS IN COLOMBIA (2012)
AbstractThe retail business in Colombia in recent years has had a remarkable evolution with the entry of new players across the country, which has allowed consumers to select the best option. Thus, strategies that have diversified retail business in order to retain and win new customers.